Thinking of the Moving body in motion as the starting point for the fashion design (Al-Academy, 2024)
Blocks and garment patterns serve as visual depictions of the human form. Despite pattern cutting's inherent flexibility and adaptability, this discipline has continually chosen to design garments that conform to the body's stationary, upright posture. Although the deep-rooted paradigm has achieved many successes, the positions that the body takes when in motion are one of the main reasons why clothing pressure increases dramatically, leading to a feeling of discomfort. The objective of this work is to depict the human body as a dynamic entity by creating a mannequin that combines all the motions produced by the body on a daily basis.The design of this methodology is based on qualitative methods, using techniques such as self-portraiture, theoretical sampling, visual somatometry, and body shape averaging. Subsequently, a collection of blocks was devised for standard articles of clothing crafted from woven fabrics. These blocks had 'distorted' shapes that conform to the curves and lines of the mobile human form, as mirrored by the mannequin. Ultimately, in order to verify the notion, the lady tested the muslin prototypes created from the designs by wearing them and confirmed that they exhibit the same expansion and contraction as the muscles and skin.